Cellular analysis of trophoblast and placenta. (November 2017) - Wong, Frances; Cox, Brian J.
Abstract: The placenta is composed of two lineages: the trophoblast and mesoderm. While morphological assessment of the placenta has highlighted major cell types and developmental structures, the human placenta is relatively unexplained on a molecular level. Current molecular analysis of the placenta has largely been confined to assessing whole organs that include both cell lineages and their differentiated progeny. This has confounded our understanding of the processes of placental development and function for two reasons. First, it is difficult to delineate the specific molecular contribution from each tissue layer or cell type. Second, it is challenging to determine if gene expression influenced by development or pathology reflect changes in all cells or subsets of cells. Applications of classic techniques for single cell analysis are now being combined with emerging technologies in high throughput analysis, such as sequencing and antibody production and screening. These combinations are leading to a new powerful paradigm for developmental and pathological research. In this review we describe techniques in cellular analysis of tissues and their application to investigation of the development of the placenta and trophoblast. Additionally we review and consider how these approaches may aid the search for stable primary cultures of human trophoblast stem cells and progenitors. Highlights: Review of techniques for preparation of tissues for single cell analysis. Review of technique in analysis of single cells, including affinity purification, flow cytometry and histology. Review of application of single cell analysis to placenta and trophoblast research.